Marketing assessment of the potential of the Russian pharmaceutical market in the framework of etiotropic therapy of children with campylobacteriosis - D. D. Demchenko; K. D. Ermolenko; Yu. V. Lobzin; I. A. Narkevich; O. D. Nemyatykh; V. N. Timchenko; Yu. V. Matlashevskaya (LLC "Diagnostics and Vaccines", 2022)
The paper analyzes approaches to etiotropic therapy and structural assessment of the range of drugs for the treatment of campylobacteriosis in children. The methods of content analysis, grouping, data aggregation, comparative and marketing analysis were used. The information base of the study was the State Register of Medicines, federal clinical guidelines for the provision of medical care to children with campylobacteriosis, European and American clinical guidelines, as well as instructions for the medical use of drugs.Comparative analysis showed that Russian clinical guidelines contain 15 international non-proprietary names used for the etiotropic therapy of campylobacteriosis. The analysis carried out by drug producing countries shows that the leading positions in the supply structure are occupied by Russian producers (68.26%). Structuring by dosage forms makes it possible to single out tablet positions (47.46%). At the same time, 36.47% of the range of drugs are approved for use from the age of 12, which limits the implementation of modern approaches to the rational etiotropic therapy of campylobacteriosis in pediatrics. Structural analysis of the range of pharmaceutical substances identifies a significant contribution to the structure of imports of Chinese producers (46.30%), which, in turn, justifies the prospects for import substitution. Solving the problem of improving the quality of medical care for children with campylobacteriosis determines the prospects for further research based on the principles of evidence-based medicine using the tools of mathematical-statistical and pharmacoeconomic analyses.